Acute and long-term effects of VX in rat brain cell aggregate culture. (February 2022) - Sawyer, Thomas W.; Wang, Yushan; Villanueva, Mercy; Song, Yanfeng; Hennes, Grant
Abstract: The contact poison VX (O-ethyl S-(2-diisopropylaminoethyl) methylphosphonothioate) is a chemical warfare agent that is one of the most toxic organophosphorus compounds known. Its primary mechanism of toxic action is through the inhibition of acetylcholinesterase and resultant respiratory paralysis. The majority of work on VX has thus concentrated on its potent anticholinesterase activity and acute toxicity, with few studies investigating potential long-term effects. In this report we describe the effects of VX in aggregating rat brain cell cultures out to 28 days post-exposure. Cholinesterase activity was rapidly inhibited (60 min IC50 = 0.73 +/− 0.27 nM), but recovered towards baseline values over the next four weeks. Apoptotic cell death, as measured using caspase-3 activity was evident only at 100 μM concentrations. Cell type specific enzymatic markers (glutamine synthase, choline acetyltransferase and 2′, 3′-cyclic nucleotide 3′-phosphodiesterase) showed no significant changes. Total Akt levels were unchanged, while an increased phosphorylation of this protein was noted only at the highest VX concentration on the first day post-exposure. In contrast, significant and delayed (28 days post-exposure) decreases were noted in vascular endothelial growth factor (VEGF) levels, a protein whose reduced levels are known to contribute to neurodegenerative disorders. These observations may indicate that the long-term effects noted in some survivors of nerve agent intoxication may be due to VX-induced declines in brain VEGF levels. Highlights: Brain cell aggregates are comprised of all major brain cell types. VX treatment rapidly inhibits acetylcholinesterase, which then recovers. VX treatment causes a delayed inhibition of vascular endothelial growth factor.